Evaluasi Program Pelayanan Administrasi Kependudukan Siap Melayani Identitas Dan Pencatatan Sipil Di Kabupaten Buleleng - Gede Gangga Bertha Aditya Prana; I Ketut Winayaa; Putu Eka Purnamaningsih (Ethics and Law Journal: Business and Notary, 2023)
ABSTRACT Public services are an important aspect of the government system, because the government is basically a servant of the community. Population Administration Services are one of the basics of the public service system, however, the problem of heterogeneous conditions causes problems for the community in population administration services. Therefore, DISDUKCAPIL Buleleng Regency implemented the SIMELIK program with a pick-up and drop-off system in population administration services. This research was conducted in 8 sub-districts in Buleleng Regency. The informants for this research consisted of 1) Head of SIMELIK's population administration and civil registration services in Buleleng Regency; 2) Head of population registration services; 3) Coordinator of SIMELIK population administration services; 4) the target community for the SIMELIK program. Data collection techniques were carried out by conducting interviews and observations. The data analysis technique used was qualitative descriptive analysis. The results of this research show that the program implementation has been running effectively and efficiently because it has been able to increase service targets to the community. The community can be reached more widely and more evenly through scheduled services. However, there are obstacles in implementing the program where the socialization carried out does not reach a wide range so that most people do not know about the program being implemented. Another obstacle is that the equipment used is classified as old, so it is necessary to rejuvenate the equipment used to provide services. Another obstacle is the lack of energy used so that it has not been able to reach a wider and optimal reach.